Abstract 4 Umbilical Cord-Derived Mesenchymal Stromal Cells Suppress Neuroinflammation and Promote Remyelination in the Spinal Cord. (6th September 2022) - Min, Hyunjung; Xu, Li; Parrott, Roberta; Kurtzberg, Joanne; Filiano, Anthony
Abstract: Introduction: Mesenchymal stromal cells (MSCs) are one of the most widely tested cell therapies due to their ability to suppress inflammation. Demyelinating diseases of the central nervous system (CNS) are commonly accompanied by neuroinflammation, including infiltrating proinflammatory leukocytes and activation of resident macrophages (microglia and border-associated macrophages in the meninges). The precise mechanism of how MSCs suppress neuroinflammation is unclear; however, we recently described a novel pathway where MSCs physically interact with macrophages to reprogram the immune response through the transfer of a cytoplasmic organelle called a processing body (p-body). Objective: We set out to study how human umbilical cord tissue-derived MSCs interact with CNS microglia and border macrophages to protect in a mouse model of spinal cord demyelination. Methods: We manufactured several MSC lines under GMP conditions and tested their ability to interact with CNS macrophages and promote remyelination in multiple preclinical assays. To determine if p-bodies are critical for these steps, we depleted p-bodies using CRISPR/Cas9 targeting to DDX6. To test for effects on acute demyelination, we injected lysophosphatidylcholine (LPC) into the spinal cord or added LPC to organotypic cerebellar slice cultures. To test direct effects on microglia activation, we treated primary microglia or a microglia cell line with lipopolysaccharide. Results: We determined that MSC promoted remyelination in the spinal cord and that this was dependent on p-bodies. MSC directly contacted CNS macrophages and inhibited their activation. Using primary microglia and a microglia cell line, we determined that MSCs suppress the release of proinflammation cytokines, IL-6, and TNF. Discussion: We determined that MSCs suppress microglial cell activation and enhance remyelination of the spinal cord. Our study offers insight into a novel mechanism about how MSCs can alter the immune response via transferring p-bodies and enhance remyelination in CNS. Furthermore, our results may lead to a quick and simple potency assay to establish the efficacy of MSCs for suppressing neuroinflammation.